2016
DOI: 10.1007/s12517-016-2441-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of model parameters, topography, and scale on the mass movement processes of debris avalanches using the discrete element method

Abstract: The mass movement process of a debris avalanche is a complex dynamic system and is influenced by topographic conditions, material composition, sliding-bed surface conditions and other factors. A discrete element method is used to simulate the mass movement process of debris avalanches and is validated by laboratory flume tests. Sensitivity analyses for the model parameters show that a low bond strength indicates that a small impact force can lead to slope failure. The friction coefficient has a little effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The studies found that the impact force on the protective structure is related to the scale, impact angle, and velocity of the landslide [22]. These factors affecting the impact force are not only influenced by terrain conditions such as slope angle, slope friction, and sliding surface [22,23] but also controlled by the composition and mechanical properties of geomaterials [23]. Some preliminary estimation methods have been proposed based on experiments and analysis [22].…”
Section: Introductionmentioning
confidence: 99%
“…The studies found that the impact force on the protective structure is related to the scale, impact angle, and velocity of the landslide [22]. These factors affecting the impact force are not only influenced by terrain conditions such as slope angle, slope friction, and sliding surface [22,23] but also controlled by the composition and mechanical properties of geomaterials [23]. Some preliminary estimation methods have been proposed based on experiments and analysis [22].…”
Section: Introductionmentioning
confidence: 99%